The Influence of Integrity, Collaboration, and Service Culture on Work Professionalism among Academic Staff at ITKES Wiyata Husada Samarinda - Agung Solihin; Achmad Tarmizi (Jurnal Multidisiplin Sahombu, 2026)
This study examines the influence of integrity, collaboration, and service culture on work professionalism among academic staff at ITKES Wiyata Husada Samarinda. Professionalism in higher education is increasingly recognized as a multidimensional construct shaped not only by individual competence but also by ethical values, relational dynamics, and institutional culture. Using a quantitative explanatory design, data were collected from 50 academic staff members through a structured questionnaire and analyzed using multiple linear regression. The findings reveal that integrity, collaboration, and service culture significantly influence work professionalism both partially and simultaneously. Service culture emerged as the most dominant predictor, indicating that institutional service orientation plays a critical role in reinforcing professional conduct within health higher education institutions. The model demonstrates substantial explanatory power, confirming that professionalism is embedded within ethical, collaborative, and cultural organizational mechanisms. This study contributes to organizational behavior literature by integrating these determinants within a unified empirical framework in the context of higher education. The findings provide strategic implications for institutional governance, particularly in strengthening ethical reinforcement programs, collaborative practices, and service excellence standards to enhance sustainable academic professionalism.